Literasi dan Inklusi Keuangan Pengusaha Lokal Anyaman di Sumba Timur - Kelen, Lusianus; Renggo, Yuniarti Reny; Ramompas, Yuvensius; Putra, Jovan Imanuel; Todo, Grasela Evarista (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Financial literacy and inclusion are the keys to business success, especially in managing finances well. This research aims to provide an overview of financial literacy and inclusion of local woven entrepreneurs in East Sumba Regency. The sample used was 78 respondents using a purposive sampling technique, spread across three weaving centers in East Sumba Regency, namely Mbatakapidu Village, Malumbi Village, and Kotak Kawau Village, using descriptive analysis techniques. The conclusion of this research is that the level of literacy understanding and financial inclusion of local woven entrepreneurs in East Sumba Regency is categorized as good, but the financial practices carried out by entrepreneurs tend to be carried out less well.